The Compleat Lextutor Application Tool for Academic and Technological Lexical Learning: Review and Bibliometric Approach - Amirullah Abduh; Ade Mulianah; Besse Darmawati; Fairul Zabadi; Umar Sidik; Wuri Handoko; Karta Jayadi; Rosmaladewi Rosmaladewi (Universitas Pendidikan Indonesia, 2023)
This research aims to portray the current representation of the term “technology” in association with other related terms in language education. The method used for this study is the combination of content analysis representation of both compleat lextutor analytical tool and bibliometric approach. The finding of the research is that four basic areas relate to language and technology in language training: multiculturalism and technology become a central theme; the technology in language skill, knowledge, and assessment; technology and thinking; and technology in language and linguistics. This research implies that educators should be able to utilize available practical technological tools for teaching, learning, analyzing, and modeling language education. Further, this research has been limited to the area of published manuscripts of language education which may cover specifically non-empirical primary data. Therefore, further empirical research may bolster the current findings of the bibliometric research on language and technology in language education.